BONUM COMMUNE SEBAGAI SASARAN GERAKAN BURUH MENURUT AJARAN SOSIAL GEREJA - Nadeak, Largus G. (UNIKA Santo Thomas, 2002)
The labourersâ€™ numbers have increased in line with the development ofindustrialization. But this development did not parallel to the appreciationon the fruit of the labourersâ€™ work. Since long labourers become theobject of work and violence. Church social teaching has anticipatedlabourersâ€™ problem since the year 1891 through the Encyclical letterâ€œRerum Novarumâ€. Itâ€™s main point is that man is homo laborans. Whenhuman put in on the job, they will fulfil their needs and also form theirself-integrity. Therefore menâ€™s/womenâ€™s job must be paid in a properpayment in accordance to the fruit of their work and ability of enterprise.Communion secure and prosperous should be the aim of this movement.Bonum Commune gives assurance to the rights of every human asindividual, and right of every human in the certain social communities.The church social teaching should be the light on the labourersâ€™movement to make a change in an injustice toward bonum commune.